A modular architecture for organizing, processing and sharing neurophysiology data - Bonacchi, Niccolò; Chapuis, Gaelle A.; Churchland, Anne K.; DeWitt, Eric E. J.; Faulkner, Mayo; Harris, Kenneth D.; Huntenburg, Julia M.; Hunter, Max; Laranjeira, Inês C.; Rossant, Cyrille; Sasaki, Maho; Schartner, Michael M.; et al. (Nature Methods, 2023)
We describe an architecture for organizing, integrating and sharing neurophysiology data within a single laboratory or across a group of collaborators. It comprises a database linking data files to metadata and electronic laboratory notes; a module collecting data from multiple laboratories into one location; a protocol for searching and sharing data and a module for automatic analyses that populates a website. These modules can be used together or individually, by single laboratories or worldwide collaborations. A modular architecture for managing and sharing electrophysiology, behavior, colony management and other data has been built to support individual laboratories or large consortia.